Question
upstudy study bank question image url

Solve for \( x \) a) \( 5^{x}=25 \) d) \( 2^{8}=4^{x} \) g) \( \frac{1}{2^{x}}=8 \) j) \( -2^{x}=-32 \) m) \( 5^{-2}=\frac{1}{25^{x}} \) p) \( 3^{x-2}=\frac{1}{3^{x}} \) s) \( 10^{x}=1 \) v) \( 27^{x-2}=81^{2 x+1} \)

Ask by Nichols Hilton. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the solutions for each equation: a) \( x = 2 \) d) \( x = 4 \) g) \( x = -3 \) j) \( x = 5 \) m) \( x = 1 \) p) \( x = 1 \) s) \( x = 0 \) v) \( x = -2 \)

Solution

Solve the equation by following steps: - step0: Solve for \(x\): \(-2^{x}=-32\) - step1: Change the signs: \(2^{x}=32\) - step2: Rewrite in exponential form: \(2^{x}=2^{5}\) - step3: Set the exponents equal: \(x=5\) Solve the equation \( 2^{8}=4^{x} \). Solve the equation by following steps: - step0: Solve for \(x\): \(2^{8}=4^{x}\) - step1: Swap the sides: \(4^{x}=2^{8}\) - step2: Rewrite in exponential form: \(2^{2x}=2^{8}\) - step3: Set the exponents equal: \(2x=8\) - step4: Divide both sides: \(\frac{2x}{2}=\frac{8}{2}\) - step5: Divide the numbers: \(x=4\) Solve the equation \( 27^{x-2}=81^{2 x+1} \). Solve the equation by following steps: - step0: Solve for \(x\): \(27^{x-2}=81^{2x+1}\) - step1: Rewrite the expression: \(3^{3x-6}=3^{8x+4}\) - step2: Set the exponents equal: \(3x-6=8x+4\) - step3: Move the expression to the left side: \(3x-8x=4+6\) - step4: Add and subtract: \(-5x=4+6\) - step5: Add and subtract: \(-5x=10\) - step6: Change the signs: \(5x=-10\) - step7: Divide both sides: \(\frac{5x}{5}=\frac{-10}{5}\) - step8: Divide the numbers: \(x=-2\) Solve the equation \( \frac{1}{2^{x}}=8 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{1}{2^{x}}=8\) - step1: Rearrange the terms: \(2^{-x}=8\) - step2: Rewrite in exponential form: \(2^{-x}=2^{3}\) - step3: Set the exponents equal: \(-x=3\) - step4: Change the signs: \(x=-3\) Solve the equation \( 5^{x}=25 \). Solve the equation by following steps: - step0: Solve for \(x\): \(5^{x}=25\) - step1: Rewrite in exponential form: \(5^{x}=5^{2}\) - step2: Set the exponents equal: \(x=2\) Solve the equation \( 3^{x-2}=\frac{1}{3^{x}} \). Solve the equation by following steps: - step0: Solve for \(x\): \(3^{x-2}=\frac{1}{3^{x}}\) - step1: Rewrite the expression: \(3^{x-2}=3^{-x}\) - step2: Set the exponents equal: \(x-2=-x\) - step3: Move the variable to the left side: \(x-2+x=0\) - step4: Add the terms: \(2x-2=0\) - step5: Move the constant to the right side: \(2x=0+2\) - step6: Remove 0: \(2x=2\) - step7: Divide both sides: \(\frac{2x}{2}=\frac{2}{2}\) - step8: Divide the numbers: \(x=1\) Solve the equation \( 10^{x}=1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(10^{x}=1\) - step1: Rewrite in exponential form: \(10^{x}=10^{0}\) - step2: Set the exponents equal: \(x=0\) Solve the equation \( 5^{-2}=\frac{1}{25^{x}} \). Solve the equation by following steps: - step0: Solve for \(x\): \(5^{-2}=\frac{1}{25^{x}}\) - step1: Rearrange the terms: \(5^{-2}=25^{-x}\) - step2: Swap the sides: \(25^{-x}=5^{-2}\) - step3: Rewrite in exponential form: \(5^{-2x}=5^{-2}\) - step4: Set the exponents equal: \(-2x=-2\) - step5: Change the signs: \(2x=2\) - step6: Divide both sides: \(\frac{2x}{2}=\frac{2}{2}\) - step7: Divide the numbers: \(x=1\) Here are the solutions for each equation: a) \( 5^{x} = 25 \) - Solution: \( x = 2 \) d) \( 2^{8} = 4^{x} \) - Solution: \( x = 4 \) g) \( \frac{1}{2^{x}} = 8 \) - Solution: \( x = -3 \) j) \( -2^{x} = -32 \) - Solution: \( x = 5 \) m) \( 5^{-2} = \frac{1}{25^{x}} \) - Solution: \( x = 1 \) p) \( 3^{x-2} = \frac{1}{3^{x}} \) - Solution: \( x = 1 \) s) \( 10^{x} = 1 \) - Solution: \( x = 0 \) v) \( 27^{x-2} = 81^{2x+1} \) - Solution: \( x = -2 \) If you have any further questions or need additional assistance, feel free to ask!

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve for \( x \) in each equation, here are the solutions: a) \( 5^{x} = 25 \) Since \( 25 = 5^{2} \), we can equate the exponents: \( x = 2 \). d) \( 2^{8} = 4^{x} \) Rewrite \( 4 \) as \( 2^{2} \): \( 2^{8} = (2^{2})^{x} \) This simplifies to \( 2^{8} = 2^{2x} \). Setting the exponents equal gives \( 8 = 2x \), so \( x = 4 \). g) \( \frac{1}{2^{x}} = 8 \) Rewrite \( 8 \) as \( 2^{3} \): \( \frac{1}{2^{x}} = 2^{3} \) can be written as \( 2^{-x} = 2^{3} \). Setting exponents gives \( -x = 3 \), thus \( x = -3 \). j) \( -2^{x} = -32 \) Remove the negative signs: \( 2^{x} = 32 \) which is \( 2^{5} \). Therefore, \( x = 5 \). m) \( 5^{-2} = \frac{1}{25^{x}} \) Since \( 25 = 5^{2} \), we have \( 25^{x} = (5^{2})^{x} = 5^{2x} \) and can rewrite the left side as: \( 5^{-2} = 5^{-2x} \). This yields \( -2 = -2x \), so \( x = 1 \). p) \( 3^{x-2} = \frac{1}{3^{x}} \) Rewrite \(\frac{1}{3^{x}}\) as \(3^{-x}\): That gives us \( 3^{x-2} = 3^{-x} \). Setting exponents equal yields \( x - 2 = -x \), so \( 2x = 2 \) and \( x = 1 \). s) \( 10^{x} = 1 \) Since \( 1 = 10^{0} \), we have: \( x = 0 \). v) \( 27^{x-2} = 81^{2x+1} \) Rewrite \( 27 \) as \( 3^{3} \) and \( 81 \) as \( 3^{4} \): This gives us \( (3^3)^{x-2} = (3^4)^{2x+1} \) or \( 3^{3(x-2)} = 3^{4(2x+1)} \). Thus, \( 3(x - 2) = 4(2x + 1) \), simplifying to: \( 3x - 6 = 8x + 4 \), leading to \( -5x = 10 \), so \( x = -2 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy